2022
DOI: 10.21608/aimj.2022.104869.1648
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study between Ultrasound Guided Quadratus Lumborum Plane Block Versus Ultrasound Guided Erector Spinae Plane Block for Postoperative Pain Relief in Patients undergoing Elective Caesarean Section

Abstract: Background: For elective cesarean birth, the anesthetic technique of preference is neuraxial anesthesia (primarily spinal anaesthesia). Adequate postsurgical analgesia is a key component of ERAS protocols; it's much more important for women who are having a cesarean birth, and it's quickly acquiring popularity. Aim of The Work:To assess the effectiveness of quadrates lumborum plane block versus Erector Spinae Plane Block as a post-operative analgesic following cesarean section. Patients and Methods: A prospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
3
0
0
Order By: Relevance
“…NRS at 6, 24 hour was significantly less in ESPB and QLBs versus group C (P value< 0.05) and was similar between ESPB and QLBs. Similar to our findings, Elkotory et al, [20] reported insignificant difference regarding pain score between QLB and ESB. Our results are compatible with Kang et al, (2021) [21] who demonstrated insignificant differences in resting pain scores at 24, 48 and 72 h postoperationly between ESPB and QLBs.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…NRS at 6, 24 hour was significantly less in ESPB and QLBs versus group C (P value< 0.05) and was similar between ESPB and QLBs. Similar to our findings, Elkotory et al, [20] reported insignificant difference regarding pain score between QLB and ESB. Our results are compatible with Kang et al, (2021) [21] who demonstrated insignificant differences in resting pain scores at 24, 48 and 72 h postoperationly between ESPB and QLBs.…”
Section: Discussionsupporting
confidence: 92%
“…In the same line with our findings, Abd Ellatif and Abdelnaby [19] noticed that the time of performing the block was statistically significant shorter (5.64±0.66 vs. 9.36±1.0 p< 0.001) in ESPB versus QLB. Regarding hemodynamics, our results are supported by Elkotory et al, [20] who observed that there was no noticeable variation in intraoperative MAP or HR between the two groups. Our results are in agreement with Abd Ellatif and Abdelnaby [19] who reported that the No noticeable variation was found between the groups in terms of MAP or HR at baseline, immediately following induction, or twenty minutes after induction; however, MAP was significantly less in the QLB and ESPBs versus the controls at forty minutes, one hour, and two hours, and postoperative.…”
Section: Discussionsupporting
confidence: 87%
“…Also, Mohamed et al reported insignificant statistical differences in the me MAP and HR intraoperatively between the ESPB and QLPB groups. 9,11,12,13 According to our results, postoperative VAS measurements at 15 min, 30 min, and 12 h were significantly reduced in the PVPB group than in the ESPB group and QL3 group. They were significantly greater in the PVPB group than the ESPB group and QL3 group at 6 h postoperatively, with insignificant variations across the 3 groups at 2 and 24 h. Postoperative VAS measurements always were insignificantly different between the ESPB group and QL3 group.…”
Section: Discussionsupporting
confidence: 55%